Incorporating phosphorus cycling into global modeling efforts: a worthwhile, tractable endeavor. Issue 2 (25th June 2015) - Reed, Sasha C.; Yang, Xiaojuan; Thornton, Peter E.
Summary: Myriad field, laboratory, and modeling studies show that nutrient availability plays a fundamental role in regulating CO2 exchange between the Earth's biosphere and atmosphere, and in determining how carbon pools and fluxes respond to climatic change. Accordingly, global models that incorporate coupled climate–carbon cycle feedbacks made a significant advance with the introduction of a prognostic nitrogen cycle. Here we propose that incorporating phosphorus cycling represents an important next step in coupled climate–carbon cycling model development, particularly for lowland tropical forests where phosphorus availability is often presumed to limit primary production. We highlight challenges to including phosphorus in modeling efforts and provide suggestions for how to move forward. Contents Summary 324 I. Introduction 324 II. A need for phosphorus in global models 325 III. Considerations for including phosphorus 326 IV. Opportunities for moving forward 327 Acknowledgements 328 References 328